Pengupahan dalam Sistem Upah Indonesia dan Islam - Ghofur, Ruslan Abdul (al-'adalah, 2018)
The conflict between workers and employers has become a routine phenomenon in the world of labor in Indonesia. From a number of demands that have arisen in each demonstration, the issue of wages has always been the main issue voiced by the workers. The government has actually attempted to mediate this issue by issuing a regulation on Provincial Minimum Wages (UMP) and Minimum Wages for City/District (UMK). The issue of wages, however, always ranks first in the demands of the workers. This article compares the concept of wages in the capitalistic economic system with the concept of wages in Islam. The aim is to get an idea of how each system regulates the relationship between workers and employers. This study finds out that in Islamic economics, wages (ujrah) are product of a system of cooperative help which is manifested in a contract of an employment agreement. Whereas in a capitalistic economic system, labor is more valued as one type of commodity or capital goods that will produce a new value.